PENGEMBANGAN MEDIA PEMBELAJARAN DIORAMA BERBANTUAN GAME TEKA-TEKI SILANG BERBASIS KEARIFAN LOKAL MUATAN IPAS KELAS III DI SDN 2 GUNUNGSARI - Baiq Farisa Dila; Nurhasannah; Muhammad Sobri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a learning media in the form of a diorama assisted by a crossword puzzle game based on local wisdom for the IPAS subject that is feasible to use. The development model used in this study is the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. Data collection techniques employed in this study include observation, documentation, and questionnaires. Data analysis was carried out using quantitative and qualitative approaches, utilizing a scoring tabel with percentage criteria to determine the feasibility of the learning media. The results showed that the material expert validator obtained an average score of 82.85%, the media expert validator obtained an average score of 96.66%, and student responses achieved a score of 91.42%. Based on the results of material expert validation, media expert validation, and student responses, it can be concluded that the diorama learning media assisted by a crossword puzzle game based on local wisdom is categorized as very feasible for use in the learning process for third-grade students.